An IoT Based Worker Safety Helmet Using Cloud Computing Technology - Khamis, Yuthriya Iddi; Alawi, Mahmoud; Athumani, Ramadhan; Sanya, Waheed Muhammad (Tanzania Journal of Engineering and Technology, 2022)
Miner safety and security is a major challenge around the world due to the exposure to toxic gases that are frequently released in underground mines. Miners' health is adversely affected primarily by toxic gases, which endanger the workers' lives. Furthermore, human sensory abilities do not detect these dangerous gases. As a result, this paper proposes a safety monitoring system that includes a temperature sensor, humidity sensor, and gas sensors to detect harmful gases and alert miners to those harmful gases using the smart helmet they wear. These gases are transmitted to the control station via the cloud using Internet of Things devices. The station monitors parameters like temperature, humidity, and toxic gases like methane and carbon monoxide to detect any abnormalities and alert the miner via a buzzer on the helmet. The data is processed by the Thing Speak cloud, which enables users to communicate via internet-connected devices and displays a field graph of the transmitted data. Keywords: safety, mining, helmet, toxic gases, temperature sensor